Informal Caregivers’ Needs in Post-Stroke Home Care: Insights from Focus Groups Conducted in Portugal Within the CaregIVR Project - Helena Josè; Martina Giusti; Lara Costa e Silva; Diogo João Tomás; Susana Ganhão-Arranhado; Carla Silva; Luís Manuel Mote de Sousa (Nursing Reports, 2026)
Background/objectives: This study aimed to identify and categorise the educational, training, and support needs of informal caregivers of stroke survivors in order to inform the development of an Immersive Virtual Reality (IVR) intervention within the European caregIVR project (Project No. 101129454; EU4Health Programme). Methods: A qualitative descriptive study was conducted using three focus groups involving informal caregivers, healthcare professionals and other stakeholders, and academics and healthcare students in Portugal (n = 33). Discussions explored everyday caregiving challenges, priority educational needs, and expectations regarding digital support tools. Data were analysed using qualitative content analysis with an inductive–deductive coding strategy supported by NVivo software (version 14). Results: Participants identified the transition from hospital to home as the most critical stage of the caregiving journey, characterised by poor continuity of care and insufficient preparation before hospital discharge. Major challenges included limited stroke-related health literacy, difficulties adapting the home environment, and substantial emotional, financial, and social burdens that frequently resulted in social isolation and caregiver burnout. Participants regarded IVR as a promising educational strategy for delivering practical, repetitive, and low-risk skills training. Conclusions: The findings suggest that caregiver empowerment should be promoted through progressive, person-centred, and non-judgemental educational programmes tailored to caregivers’ evolving needs. Caregivers should be supported by multidisciplinary teams capable of addressing the clinical, practical, and psychosocial complexity of post-stroke home care. Rather than replacing professional support, IVR should be considered a complementary educational tool with the potential to improve caregivers’ preparedness, confidence, and safety in the home-care setting.